2012
DOI: 10.1007/s00894-012-1723-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on electronic structures and optical properties of indoline and triphenylamine dye sensitizers for solar cells

Abstract: The computations of the geometries, electronic structures, dipole moments and polarizabilities for indoline and triphenylamine (TPA) based dye sensitizers, including D102, D131, D149, D205, TPAR1, TPAR2, TPAR4, and TPAR5, were performed using density functional theory, and the electronic absorption properties were investigated via time-dependent density functional theory with polarizable continuum model for solvent effects. The population analysis indicates that the donating electron capability of TPA is bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…Similar results are also found for several dye sensitizers [19,[62][63][64]. The discrepancy between experiment and TD-DFT calculations may be attributed to DFT and solvent effects [61]. Though the discrepancy is existed, the TD-DFT calculations are capable of describing the spectral features because of the qualitative agreement of line shape and relative strength as compared with experiment.…”
Section: Electronic Absorption Spectra and Sensitized Mechanismsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results are also found for several dye sensitizers [19,[62][63][64]. The discrepancy between experiment and TD-DFT calculations may be attributed to DFT and solvent effects [61]. Though the discrepancy is existed, the TD-DFT calculations are capable of describing the spectral features because of the qualitative agreement of line shape and relative strength as compared with experiment.…”
Section: Electronic Absorption Spectra and Sensitized Mechanismsupporting
confidence: 76%
“…The calculated isotropic polarizability of TA-St-CA is slightly less than that of D5 (510.6 a.u. [61]). This may be resulted from that the aromaticity of the phenyl group in conjugate bridge of TA-St-CA is stronger than that of thiophene group in D5, and then the electronic structure of phenyl group is more stable than that of thiophene group, thus the response of external field for TA-St-CA is weaker than that for D5.…”
Section: Polarizability and Hyperpolarizabilitymentioning
confidence: 93%
“…Therefore, the substitution at ortho-positions of the meso-phenyls has slight effects on the geometry of porphyrins framework. In addition, the quasi-coplanarity between acceptor group (carboxylic acid moiety) and conjugate bridge is favorable for intramolecular charge transfer (IMCT) [64]. The twist between diarylamino group and porphyrin cycle, which results from the orbital hybridiazation of N in diarylamino group, limits the electron donating ability [48].…”
Section: Resultsmentioning
confidence: 99%
“…They determine not only the strength of molecular interactions (long-range intermolecular induction, dispersion 16 . It has been found that the dye sensitizer hemicyanine system, which has high NLO property, usually possesses high photoelectric conversion performance.…”
Section: Polarizability and Hyperpolarizabilitymentioning
confidence: 99%